2010
DOI: 10.1073/pnas.1001823107
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Arp3 expression in the testis prevents blood–testis barrier disruption during junction restructuring at spermatogenesis

Abstract: In epithelia, a primary damage of tight junctions (TJ) always leads to a secondary disruption of adherens junction (AJ), and vice versa. This response, if occurring in the testis, would disrupt spermatogenesis because the blood-testis barrier (BTB) must remain intact during the transit of spermatids in the seminiferous epithelium, which is associated with extensive apical ectoplasmic specialization (apical ES, a testis-specific AJ type) restructuring. As such, apical ES restructuring accompanied with the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 133 publications
(189 citation statements)
references
References 26 publications
8
181
0
Order By: Relevance
“…It is thus conceivable that these actin filament bundles at the apical ES require continuous but highly restrictive spatiotemporal breakdown and reorganization via cycles of "debundling" and "rebundling," such that spermatids can be transported across the seminiferous epithelium while remaining attached to the Sertoli cell. Recent studies have shown that such extensive reorganization of the F-actin network at the apical ES is regulated via stage-specific and spatiotemporal expression of two major groups of actin regulatory proteins in the seminiferous epithelium: 1) actin bundling Eps8 (also an actin-barbed end-capping protein) (13) and palladin (also an actin crosslinking protein) (25); and 2) branched actin polymerization protein Arp3 (12), effectively converting actin filaments from their bundled to their "branched/debundled" configuration and vice versa. While these recent findings have shed insightful information on the regulation of apical ES dynamics during spermatogenesis, such as the role of actin-bundling proteins Eps8 and palladin, and actin branched polymerization/debundling regulatory proteins Arp3 and drebrin E, the underlying molecular mechanism(s) and the involving biomolecule(s) that trigger these events remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus conceivable that these actin filament bundles at the apical ES require continuous but highly restrictive spatiotemporal breakdown and reorganization via cycles of "debundling" and "rebundling," such that spermatids can be transported across the seminiferous epithelium while remaining attached to the Sertoli cell. Recent studies have shown that such extensive reorganization of the F-actin network at the apical ES is regulated via stage-specific and spatiotemporal expression of two major groups of actin regulatory proteins in the seminiferous epithelium: 1) actin bundling Eps8 (also an actin-barbed end-capping protein) (13) and palladin (also an actin crosslinking protein) (25); and 2) branched actin polymerization protein Arp3 (12), effectively converting actin filaments from their bundled to their "branched/debundled" configuration and vice versa. While these recent findings have shed insightful information on the regulation of apical ES dynamics during spermatogenesis, such as the role of actin-bundling proteins Eps8 and palladin, and actin branched polymerization/debundling regulatory proteins Arp3 and drebrin E, the underlying molecular mechanism(s) and the involving biomolecule(s) that trigger these events remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the organization of actin filament bundles is dynamically regulated via the stage-specific and spatiotemporal expression of epidermal growth factor receptor pathway substrate 8 (Eps8, an actin filament barbedend capping and bundling protein) (13), palladin (an actin cross-linking and bundling protein) (25), and actin-related protein 3 (Arp3, which together with Arp2 forms the Arp2/3 complex that induces barbed end branched actin polymerization) (12). In short, these actin-binding/regulatory proteins are working synergistically to convert actin filaments at the apical ES from a bundled to a "debundled/branched" configuration and vice versa to facilitate spermatid transport across the epithelium during the epithelial cycle.…”
mentioning
confidence: 99%
“…67 The most striking observation is that the stage-specific expression of drebrin E closely resembles that reported for Arp3, 39 a component of the actin branching nucleation regulatory protein Arp2/3 complex, particularly at the apical ES. 39 More importantly, drebrin E was highly expressed at the apical ES at stage VII, 67 co-localizing with Arp3 to the concave side of the elongating spermatid head where extensive endocytic vesicle-mediated protein trafficking events are known to take place, begining at stage VII to prepare for the release of sperm at spermiation at stage VIII. 7,23 Recent studies have shown that proteins known to be involved in protein endocytosis, namely clathrin, cortactin and N-WASP, are also found at the same site.…”
Section: Acknowledgmentsmentioning
confidence: 69%
“…For instance, drebrin E and Arp3 were virtually undetectable at the apical ES at the interface of step 8-17 spermatids-Sertoli cell, but expressed intensely only at the interface of step 18-19 spermatids-Sertoli cells at stages V-VII of the epithelial cycle. 39,67 Thus, other actin bundling proteins, such as Eps8, 38 are probably maintaining the integrity of actin filament bundles (actin depolymerizing factor homology) domain family of actin-binding proteins 58 and to be involved in actin dynamics, including formation of actin bundles, 59 recruitment of proteins (e.g., chemokine receptor CXCR4) via changes in actin polymerization, 60 building of dendritic spines and stabilization of gap junctions, 61 actin remodeling via its interaction with Ras GTPases, 62 and formation of lamellipodia and filopodia. 63 Thus, drebrins have numerous cellular functions via their role as actin-binding proteins.…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation